Merger Control in Hungary - Rigó, Csaba Balázs; Tóth, András; Bodócsi, András; Buránszki, Judit; Dudra, Attila (Public Finance Quarterly, 2021)
The present study presents the findings of the most comprehensive research that has ever been conducted in relation to the 30-year-old Hungarian merger authorisation process that has been in place since the political transition in Hungary. The aim of the research is, in particular, to present to the wider professional public the development of the authorisation process for mergers (or concentrations) in Hungary, which started in the last decade, and the resulting public value returns that have been achieved. The most important results to emerge from the research are that – compared to 2010 data – the average procedure time for full-scale merger proceedings in 2020 was reduced by 62%, and the administrative time limit for simplified cases decreased by 82.5%. Furthermore, the research revealed that today one-third of the Hungarian Competition Authority’s market interventions in connection with mergers take a verbal/informal form. This study was conducted using the methodology of data processing and analysing that are at the disposal of the Hungarian Competition Authority.